Volume 1: Turbo Expo 2003 2003
DOI: 10.1115/gt2003-38777
|View full text |Cite
|
Sign up to set email alerts
|

Experiences With Microturbine Generator Systems Installed in the South Coast Air Quality Management District

Abstract: A comprehensive field data collection campaign is reported on in which operational data are being obtained from microturbine generators located in the South Coast Air Quality Management District (AQMD). The data obtained are archived in a SQL database, which provides the ability to look at various performance aspects as a function of many parameters interactively on the Internet. An overview of the program is provided along with details regarding the data collection and archiving strategies. To provide a frame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Both electric and natural gas rates were taken as of April 2002. It is important to note that the main economic conclusions of this study might change depending on the current natural gas and electricity prices, as shown in a recent economic analysis on the operating savings provided by MTGs in southern California [9]. For instance, as of September of 2004, electric rates for the hospital building are almost 40% lower and gas rates have increased 30% approximately.…”
Section: Characteristics Of the Four Buildings Templatesmentioning
confidence: 99%
“…Both electric and natural gas rates were taken as of April 2002. It is important to note that the main economic conclusions of this study might change depending on the current natural gas and electricity prices, as shown in a recent economic analysis on the operating savings provided by MTGs in southern California [9]. For instance, as of September of 2004, electric rates for the hospital building are almost 40% lower and gas rates have increased 30% approximately.…”
Section: Characteristics Of the Four Buildings Templatesmentioning
confidence: 99%
“…In the work by Ribaud [2], a thermodynamic model was developed and applied to study heat transfer characteristic in an ultra-micro turbine at different situations. McDonell et al [3] studied the performance of a micro gas turbine at various conditions, and optimum operating parameters were obtained. Further, Rodgers [4] investigated flow characteristics and aerodynamic performance of a micro gas turbine.…”
Section: Introductionmentioning
confidence: 99%